Solid electrolyte material, solid electrolyte, method for producing the same, and all-solid-state battery
Through the combination of lithium, tantalum, phosphorus and oxygen compounds and boron compounds, amorphous solid electrolyte is sintered at low temperature, which solves the problem of insufficient ion conductivity of oxide-based electrolytes at low temperatures, and improves the stability of battery materials and Economical.
Patent Information
- Application Number
- CN202180041257.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-10
- Filing Date
- 2021-06-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-06-09
AI Technical Summary
It is difficult to achieve high ion conductivity when the oxide-based solid electrolyte is sintered at low temperatures, and the positive electrode and negative electrode materials are easily decomposed or deteriorated during the firing process, affecting battery performance.
Using a combination of lithium-ion conductive compounds containing lithium, tantalum, phosphorus and oxygen, boron compounds, bismuth compounds or phosphorus compounds, it is pulverized and mixed and then sintered at low temperature to form an amorphous solid electrolyte to ensure that it can still be achieved below 900°C. Full ion conductivity.
It is possible to produce a sintered body with high ion conductivity at low temperatures, inhibiting the decomposition or deterioration of the positive electrode and negative electrode materials, and improving the economics of the battery and equipment utilization.
Smart Images

Figure BDA0003987695240000331 
Figure BDA0003987695240000351 
Figure BDA0003987695240000371
Abstract
Description
Technical Field
[0001] A technical solution of the present invention relates to a solid electrolyte material, a solid electrolyte, a method for manufacturing the same, or an all-solid-state battery. Background Art
[0002] In recent years, there has been a demand for the development of high-output and high-capacity batteries as power sources for laptop computers, tablet terminals, mobile phones, smartphones, and electric vehicles (EVs). Among them, all-solid-state batteries that use solid electrolytes instead of liquid electrolytes such as organic solvents have attracted much attention as batteries with excellent charge and discharge efficiency, charging speed, safety, and productivity.
[0003] As the above-mentioned solid electrolyte, an inorganic solid electrolyte has attracted attention, and as the inorganic solid electrolyte, mainly oxide-based and sulfide-based solid electrolytes are known.
[0004] When using sulfide-based solid electrolytes, although there are advantages such as being able to produce batteries by cold pressing, etc., they are unstable relative to humidity and may produce harmful hydrogen sulfide gas. Therefore, oxide-based solid electrolytes are being developed from the perspective of safety and other aspects.
[0005] As such an oxide-based solid electrolyte, Non-Patent Document 1 states that LiTa2PO8 having a monoclinic crystal structure exhibits high lithium ion conductivity (total conductivity (25°C): 2.5×10 -4 S cm -1 ).
[0006] Prior Art Literature
[0007] Non-patent literature 1: J. Kim et al., J. Mater. Chem. A, 2018, 6, p22478-22482 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The grain boundary resistance of oxide-based solid electrolytes is extremely high. In order to obtain ion conductivity that can be used in all-solid-state batteries, it is necessary not only to pressurize the solid electrolyte powder but also to make a high-density sintered body. In addition, in order to obtain such a high-density sintered body, it is necessary to sinter it at a high temperature of about 1100°C, for example.
[0010] In addition, when an oxide-based solid electrolyte is used to produce an all-solid-state battery, it is necessary to sinter it together with a positive electrode material, a negative electrode material, etc. in order to obtain high ion conductivity.
[0011] During these firing processes, in order to suppress the decomposition and deterioration of other materials such as the positive electrode and negative electrode materials in terms of economy or equipment, it is expected that a sintered body with high ion conductivity can be obtained even when the firing is carried out at a low temperature (for example, below 900°C). However, when LiTa2PO8 described in non-patent document 1 was fired at a low temperature, a sintered body showing sufficient ion conductivity was not obtained.
[0012] One aspect of the present invention provides a solid electrolyte material that can obtain a sintered body having sufficient ion conductivity even when sintered at a low temperature (for example, 900° C. or less).
[0013] Means for solving problems
[0014] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved according to the following technical configuration examples, thereby completing the present invention.
[0015] The technical configuration examples of the present invention are as follows.
[0016] [1] A solid electrolyte material comprising a lithium ion conductive compound (a) and a compound (b),
[0017] The lithium ion conductive compound (a) contains lithium, tantalum, phosphorus and oxygen as constituent elements,
[0018] The compound (b) is at least one selected from a boron compound, a bismuth compound and a phosphorus compound [the compound (b) is a compound different from the compound (a)].
[0019] [2] The solid electrolyte material according to [1], which is amorphous.
[0020] [3] The solid electrolyte material according to [1], wherein the compound (a) has a monoclinic crystal structure.
[0021] [4] The solid electrolyte material according to any one of [1] to [3], wherein the compound (a) has a composition formula Li 1+(5-a)x 〕Ta 2-x M1 x PO8 [M1 is one or more elements selected from Nb, Zr, Ga, Sn, Hf, W and Mo, 0.0≤x<1.0, a is the average valence of M1], or a compound represented by the composition formula Li〔 1+(5-b)y 〕Ta2P 1-y M2 y A compound represented by O8 [M2 is one or more elements selected from Si, Al and Ge, 0.0≤y<0.7, b is the average valence of M2].
[0022] [5] The solid electrolyte material according to any one of [1] to [4], wherein the compound (b) contains lithium or hydrogen as a constituent element.
[0023] [6] The solid electrolyte material according to any one of [1] to [5], wherein the content of tantalum element is 10.6 to 16.6 atomic %.
[0024] [7] The solid electrolyte material according to any one of [1] to [6], wherein the content of phosphorus is 5.3 to 8.3 atomic %.
[0025] [8] The solid electrolyte material according to any one of [1] to [7], wherein the content of lithium element is 5.0 to 20.0 atomic %.
[0026] [9] The solid electrolyte material according to any one of [1] to [8], wherein the boron compound is selected from LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 , Li 3.6 B2O 4.8 , Li 3.2 B2O 4.6 、Li4B2O5、Li6B4O9、Li 3-x5 B 1- x5 C x5 O3(0<x5<1), Li 4-x6 B 2-x6 C x6 O5(0<x6<2), Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1 At least one compound selected from BO3, B2O3 and H3BO3.
[0027]
[10] The solid electrolyte material according to any one of [1] to [9], wherein the bismuth compound is selected from LiBiO2, Li3BiO3, Li4Bi2O5, Li 2.4 Al 0.2 At least one compound of BiO3 and Bi2O3.
[0028]
[11] The solid electrolyte material according to any one of [1] to
[10] , wherein the phosphorus compound is at least one compound selected from LiPO 3 and Li 3 PO 4 .
[0029]
[12] The solid electrolyte material according to any one of [1] to
[11] , wherein the content of the compound (b) is 1 to 40 mol % relative to 100 mol % of the total of the compounds (a) and (b).
[0030]
[13] A method for producing a solid electrolyte material, wherein the solid electrolyte material is the solid electrolyte material described in any one of [1] to
[12] , the method comprising the step of pulverizing and mixing the compound (a) and the compound (b).
[0031]
[14] A solid electrolyte obtained by using the solid electrolyte material described in any one of [1] to
[12] .
[0032]
[15] A solid electrolyte which is a sintered body of the solid electrolyte material according to any one of [1] to
[12] .
[0033]
[16] A method for producing a solid electrolyte, comprising the step of calcining the solid electrolyte material described in any one of [1] to
[12] at 500 to 900° C., wherein the solid electrolyte is the solid electrolyte described in
[14] or
[15] .
[0034]
[17] A method for producing a solid electrolyte, comprising step 1 and step 2,
[0035] In the step 1, a lithium ion conductive compound (a) and a compound (b) are pulverized and mixed to prepare an amorphous solid electrolyte material, wherein the lithium ion conductive compound (a) contains lithium, tantalum, phosphorus and oxygen as constituent elements, and the compound (b) is at least one selected from a boron compound, a bismuth compound and a phosphorus compound [the compound (b) is a compound different from the compound (a)],
[0036] In the step 2, the solid electrolyte material obtained in the step 1 is calcined.
[0037]
[18] An all-solid-state battery comprising a positive electrode, a negative electrode and a solid electrolyte layer,
[0038] The positive electrode has a positive electrode active material,
[0039] The negative electrode has a negative electrode active material,
[0040] The solid electrolyte layer is located between the positive electrode and the negative electrode,
[0041] The solid electrolyte layer includes the solid electrolyte described in
[14] or
[15] .
[0042]
[19] According to the all-solid-state battery described in
[18] , the positive electrode active material comprises LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 One or more compounds in .
[0043]
[20] According to the all-solid-state battery described in
[18] or
[19] , the negative electrode active material comprises LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite.
[0044]
[21] The all-solid-state battery according to any one of
[18] to
[20] , wherein the positive electrode and the negative electrode contain the solid electrolyte described in
[14] or
[15] .
[0045] Effects of the Invention
[0046] According to one embodiment of the present invention, even if sintering is performed at a low temperature (e.g., below 900°C), a sintered body with sufficient ion conductivity, especially sufficient lithium ion conductivity, can be obtained. Therefore, by using the solid electrolyte material involved in one embodiment of the present invention, an all-solid battery can be easily produced that has excellent economic efficiency, suppresses decomposition or deterioration of other materials such as positive or negative electrode materials, and contains a solid electrolyte with sufficient ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the XRD pattern of LiTa2PO8 synthesized in Synthesis Example 1.
[0048] Figure 2 This is the XRD pattern of the Si-containing LTPO synthesized in Synthesis Example 2.
[0049] Figure 3 This is the XRD pattern of the Nb-containing LTPO synthesized in Synthesis Example 3.
[0050] Figure 4 This is the XRD pattern of the solid electrolyte material prepared in Example 1. DETAILED DESCRIPTION
[0051] 《Solid Electrolyte Materials》
[0052] A solid electrolyte material (hereinafter also referred to as "the present material") involved in one embodiment of the present invention comprises a lithium ion conductive compound (a) and a compound (b), wherein the lithium ion conductive compound (a) comprises lithium, tantalum, phosphorus and oxygen as constituent elements, and the compound (b) is at least one selected from a boron compound, a bismuth compound and a phosphorus compound [compound (b) is a compound different from compound (a)].
[0053] The present material is not particularly limited as long as it contains compound (a) and compound (b). For example, it can be manufactured by a method including a step of mixing compound (a) and compound (b). When a solid electrolyte is obtained from the present material, it is preferably manufactured by a method including a step of crushing and mixing compound (a) and compound (b) from the perspective of being able to easily obtain a solid electrolyte with higher ion conductivity.
[0054] The present material obtained by pulverizing and mixing compound (a) and compound (b) may not necessarily clearly contain compound (a) and compound (b). Even in this case, the present material obtained by pulverizing and mixing compound (a) and compound (b) is considered to contain compound (a) and compound (b).
[0055] The present material, especially the present material obtained by the above-mentioned pulverization and mixing, is preferably amorphous. The present material is amorphous, for example, when no peak is observed (a broad peak may be observed) in an X-ray diffraction (XRD) pattern.
[0056] Since the present material is amorphous, a solid electrolyte obtained from the present material, particularly a solid electrolyte (sintered body) obtained by sintering the present material, tends to exhibit higher ion conductivity.
[0057] The shape and size of the material are not particularly limited, but are preferably in the form of particles (powder). The average particle size (D50) of the material, especially the material obtained by the above-mentioned pulverization and mixing, is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm.
[0058] When the average particle size of the present material is within the above range, a solid electrolyte obtained from the present material, particularly a solid electrolyte (sintered body) obtained by sintering the present material, tends to exhibit higher ion conductivity.
[0059] The content of lithium element in the present material is preferably 5.0 to 20.0 atomic %, more preferably 9.0 to 15.0 atomic %, from the viewpoint of easily obtaining a solid electrolyte having higher lithium ion conductivity.
[0060] The content of lithium in the present material includes both lithium from compound (a) and lithium from compound (b) when a compound containing lithium is used as compound (b). The same is true for the content of other elements in the present material.
[0061] In addition, the content of each element in the present material, for example, as a lithium-containing transition metal oxide such as LiCoO2, a standard powder sample containing Mn, Co, and Ni in a ratio of 1:1:1 is used, and the absolute intensity quantitative method of Auger electron spectroscopy (AES: Auger Electron Spectroscopy) is used for determination. In addition, it can also be obtained by quantitative analysis known in the past. For example, after adding acid to the sample for thermal decomposition, the thermal decomposition product can be constant in volume, and a high-frequency inductively coupled plasma (ICP) luminescence analysis device can be used to obtain the content of each element in the present material.
[0062] The content of phosphorus in the present material is preferably 5.3 to 8.3 atomic %, more preferably 5.8 to 8.0 atomic %, from the viewpoint of easily obtaining a solid electrolyte having a higher lithium ion conductivity.
[0063] The content of tantalum in the present material is preferably 10.6 to 16.6 atomic %, more preferably 11.0 to 16.0 atomic %, from the viewpoint of easily obtaining a solid electrolyte having a higher lithium ion conductivity.
[0064] When the present material contains boron, the content of boron in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.5 to 3.0 atomic % from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.
[0065] When the present material contains bismuth element, the content of bismuth element in the present material is preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 2.0 atomic % from the viewpoint of lowering the firing temperature when obtaining a sintered body having sufficient ion conductivity.
[0066] The present material may contain a metal element M1 [at least one element selected from Nb, Zr, Ga, Sn, Hf, W and Mo]. In this case, from the perspective of being able to easily obtain a solid electrolyte with higher lithium ion conductivity, the content of the M1 element in the present material is preferably 0.1 to 5.0 atomic %, and more preferably 0.5 to 3.0 atomic %.
[0067] The present material may contain a metal element M2 [M2 is at least one element selected from Si, Al and Ge]. In this case, from the perspective of being able to easily obtain a solid electrolyte with higher lithium ion conductivity, the content of the M2 element in the present material is preferably 0.1 to 5.0 atomic %, and more preferably 0.5 to 3.0 atomic %.
[0068] <Compound (a)>
[0069] The compound (a) is a lithium ion conductive compound containing lithium, tantalum, phosphorus, and oxygen as constituent elements, and is preferably an oxide containing these elements.
[0070] The compound (a) contained in the present material may be one kind or two or more kinds.
[0071] The compound (a) before the above-mentioned pulverization and mixing is preferably a compound having a monoclinic crystal structure. Whether the compound (a) has a monoclinic crystal structure can be determined, for example, by performing a Rietveld analysis on the X-ray diffraction (XRD) pattern of the compound (a), and specifically, the method of the following embodiment can be used for determination.
[0072] When compound (a) is not a garnet-type, perovskite-type, or LISICON-type structure but a compound having a monoclinic structure, by using it together with compound (b), a sintered body with sufficient ion conductivity can be obtained even when sintered at a low temperature (e.g., below 900°C).
[0073] Furthermore, the monoclinic structure in this specification may include a rectangular crystal with a β angle of 90°. For example, the lattice constants a, b, and c of LiTa2PO8 with a monoclinic structure are The angle of β is 90.03° and the theoretical density is 5.85 (g / cm 3 ).
[0074] The monoclinic ratio of compound (a) (=monoclinic crystal amount×100 / total observed crystal amount) is preferably 70% or more, more preferably 80% or more, further preferably 90% or more, and the upper limit is not particularly limited but is 100%.
[0075] By using the compound (a) having a monoclinic fraction within the above range, there is a tendency that a solid electrolyte having high ion conductivity both within the crystal grains and at the grain boundaries can be easily obtained.
[0076] The monoclinic ratio can be determined by performing Rietveld analysis on an X-ray diffraction (XRD) pattern, and specifically, can be determined by the method of the following embodiment.
[0077] As compound (a), specifically, there can be mentioned compounds (a1) containing lithium, tantalum, phosphorus and oxygen as constituent elements and further containing one or more metal elements M1 selected from Nb, Zr, Ga, Sn, Hf, W and Mo, compounds (a2) containing lithium, tantalum, phosphorus and oxygen as constituent elements and further containing one or more metal elements M2 selected from Si, Al and Ge, etc. Among them, from the perspective of further exerting the effects of the present invention, as compound (a), preferably, the constituent elements are only composed of lithium, tantalum, phosphorus and oxygen, and more preferably LiTa2PO8.
[0078] Compound (a1)
[0079] The compound (a1) is preferably LiTa2PO8, or a compound in which a portion of Ta in LiTa2PO8 is replaced by a metal element M1, and preferably has a monoclinic structure.
[0080] Specifically, the compound (a1) is preferably composed of the formula Li 1+(5-a)x 〕Ta 2-x M1 x A compound represented by PO8 [M1 is one or more elements selected from Nb, Zr, Ga, Sn, Hf, W and Mo, 0.0≤x<1.0, a is the average valence of M1].
[0081] In the solid electrolyte obtained using the compound (a), M1 is more preferably Nb, W, or Mo, further preferably Nb and W, and particularly preferably Nb, from the viewpoint of improving lithium ion conductivity at the grain boundaries.
[0082] The above-mentioned x is preferably 0.95 or less, more preferably 0.90 or less, further preferably 0.85 or less, more preferably 0.80 or less, and particularly preferably 0.75 or less.
[0083] When x is within the above range, in the solid electrolyte obtained using the compound (a), the lithium ion conductivity at the grain boundaries tends to be improved.
[0084] The content of M1 can be obtained as the percentage of the number of atoms of M1 relative to the total number of atoms of tantalum and M1 by quantitative analysis known in the past. For example, after adding acid to compound (a) for thermal decomposition, the constant volume thermal decomposition product is obtained using a high-frequency inductively coupled plasma (ICP) luminescence analysis device. In the manufacturing method of compound (a) described later, tantalum and M1 basically do not flow out of the system, so the percentage of the number of atoms of M1 relative to the total number of atoms of tantalum and M1 can be simply calculated based on the amount of raw materials fed.
[0085] Depending on the valence and content of M1, the amount of Li varies according to the average valence of M1 to obtain charge neutrality of the compound (a). The average valence of M1 represented by a can be determined as follows.
[0086] In the case where M1 is composed of two or more elements, the above a is calculated by weighted average using the valence of each element and the content of each element. For example, in the case where M1 contains 80 atomic % of Nb and 20 atomic % of Zr, a is calculated as (+5×0.8)+(+4×0.2)=+4.8. In addition, in the case where M1 is composed of 80 atomic % of Nb and 20 atomic % of W, a is calculated as (+5×0.8)+(+6×0.2)=+5.2.
[0087] Compound (a2)
[0088] The above-mentioned compound (a2) is preferably LiTa2PO8, or a compound in which a part of P in LiTa2PO8 is replaced by a metal element M2, and preferably has a monoclinic structure.
[0089] Specifically, the compound (a2) is preferably composed of the formula Li 1+(5-b)y 〕Ta2P 1-y M2 y A compound represented by O8 [M2 is one or more elements selected from Si, Al and Ge, 0.0≤y<0.7, b is the average valence of M2].
[0090] In the solid electrolyte obtained using the compound (a), M2 is more preferably Si or Al, and even more preferably Si, from the viewpoint of improving the lithium ion conductivity at the grain boundary.
[0091] The above-mentioned y is preferably 0.65 or less, more preferably 0.60 or less, and further preferably 0.55 or less.
[0092] When y is within the above range, in the solid electrolyte obtained using the compound (a), the total conductivity, which is the sum of the lithium ion conductivity within the crystal grains and at the crystal grain boundaries, tends to be improved.
[0093] The content of M2 can be used as the percentage of the total atomic number of M2 relative to phosphorus and M2, obtained by quantitative analysis known in the past. For example, after adding acid to compound (a) for thermal decomposition, constant volume thermal decomposition product is obtained using high-frequency inductively coupled plasma (ICP) luminescence analysis device. In the manufacture method of compound (a) described later, phosphorus and M2 basically will not flow out of the system, so the percentage of the total atomic number of M2 relative to phosphorus and M2 can be simply calculated according to the charging amount of raw materials.
[0094] The average price represented by b can be calculated in the same way as the method of calculating the average price a.
[0095] [Method for producing compound (a)]
[0096] The method for producing the compound (a) is not particularly limited, and conventionally known production methods such as solid phase reaction and liquid phase reaction can be used. Specific examples of the production method include a method comprising at least one mixing step and one calcining step.
[0097] Mixing process
[0098] Examples of the mixing step include a step of mixing a lithium atom-containing compound, a tantalum atom-containing compound, a phosphorus atom-containing compound as raw materials, and, if necessary, a compound containing the metal element M1 and / or a compound containing the metal element M2.
[0099] The compound containing lithium atoms is not particularly limited, but is preferably an inorganic compound from the perspective of easy handling. Examples of inorganic compounds containing lithium atoms include lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium hydroxide (LiOH), lithium acetate (LiCH3COO) and hydrates thereof. Among them, lithium carbonate is preferably used from the perspective of easy decomposition and reaction.
[0100] The lithium atom-containing compound may be used alone or in combination of two or more.
[0101] The compound containing tantalum atoms is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling. Examples of inorganic compounds containing tantalum atoms include tantalum pentoxide (Ta2O5) and tantalum nitrate (Ta(NO3)5). Among them, tantalum pentoxide is preferred from the viewpoint of cost.
[0102] The tantalum atom-containing compound may be used alone or in combination of two or more.
[0103] The phosphorus atom-containing compound is not particularly limited, but phosphates are preferred. Examples of the phosphates include diammonium hydrogen phosphate ((NH4)2HPO4) and monoammonium dihydrogen phosphate (NH4H2PO4) from the viewpoint of easy decomposition and reaction.
[0104] The phosphorus atom-containing compound may be used alone or in combination of two or more.
[0105] The compound containing the metal element M1 is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples thereof include oxides and nitrates of M1. Among them, oxides are preferred from the viewpoint of cost.
[0106] The compound containing the metal element M1 may be used alone or in combination of two or more.
[0107] When M1 is Nb, Ga or Sn, examples of the oxide include niobium pentoxide (Nb2O5), gallium oxide (Ga2O3), tin oxide (SnO2) and the like.
[0108] When M1 is Zr, Hf, W or Mo, the oxides include zirconium oxide (ZrO2), hafnium oxide (HfO2), tungsten oxide (WO3), molybdenum oxide (MoO3), etc. When M1 is Zr, Hf, W or Mo, in addition to the oxides, zirconium hydroxide (Zr(OH)4), hafnium hydroxide (Hf(OH)4), tungstic acid (H2WO4), molybdic acid (H2MoO4) may also be used from the perspective of easy reaction.
[0109] The compound containing the metal element M2 is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples thereof include a simple substance and an oxide of M2. Among them, an oxide is preferred from the viewpoint of easy handling.
[0110] The compound containing the metal element M2 may be used alone or in combination of two or more.
[0111] When M2 is Si, Ge or Al, examples of the oxide include silicon oxide (SiO2), germanium oxide (GeO2), aluminum oxide (Al2O3) and the like.
[0112] Examples of a method for mixing the raw materials include a method of mixing using a roll mill, a ball mill, a small diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank disintegrator, a jet mill, and the like.
[0113] The mixing ratio of the raw materials may be, for example, a stoichiometric ratio that can give a desired composition of the compound (a).
[0114] In addition, in the calcination step described later, since lithium atoms are easy to flow out of the system, the above-mentioned lithium atom-containing compound can be used in excess of about 10% to 20%. In addition, in the calcination step described later, in order to suppress the generation of by-products, the above-mentioned phosphorus atom-containing compound can be used in excess of about 0.10% to 10%.
[0115] During the mixing, the mixture may be mixed while being heated as necessary, but is usually mixed at room temperature.
[0116] The mixing may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.
[0117] ·Firing process
[0118] In the above-mentioned calcining process, the mixture obtained in the mixing process is calcined. In the case of performing multiple calcining processes, in order to crush or reduce the diameter of the calcined product obtained in the calcining process, a pulverizing process using a ball mill or a mortar or the like can be provided. In particular, the reaction rate of the phase generation of compound (a) is slow, so sometimes a reaction intermediate is present in the first calcining. In this case, it is preferred to perform the first calcining, and then perform the calcining process after performing the pulverizing process.
[0119] The calcining step may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.
[0120] The calcination temperature varies depending on the calcination time, but is preferably 800 to 1200°C, more preferably 950 to 1100°C, and even more preferably 950 to 1000°C.
[0121] When the calcination temperature is within the above range, lithium atoms are less likely to flow out of the system, and a compound (a) having high ion conductivity tends to be easily obtained.
[0122] The firing time (the total firing time when the firing step is performed several times) varies depending on the firing temperature, but is preferably 1 to 16 hours, and more preferably 3 to 12 hours.
[0123] When the calcination time is within the above range, lithium atoms are less likely to flow out of the system, and a compound (a) having high ion conductivity tends to be easily obtained.
[0124] The firing step may be a two-step process of, for example, low-temperature firing and high-temperature firing.
[0125] In this case, as the low-temperature calcination, for example, calcination at 400 to 800° C. for 2 to 12 hours can be mentioned.
[0126] In order to suppress the residual by-products, high-temperature calcination may be performed twice. The calcination temperature of the second calcination step is preferably 800 to 1200°C, more preferably 950 to 1100°C, and even more preferably 950 to 1000°C.
[0127] The firing time in each firing step is preferably 1 to 8 hours, more preferably 2 to 6 hours.
[0128] The fired product obtained after the firing step may absorb moisture or react with carbon dioxide to deteriorate if left in the air. Therefore, the fired product obtained after the firing step is preferably transferred to a dehumidified inert gas atmosphere for storage when the temperature reaches 200° C. or less during the temperature drop after the firing step.
[0129] <Compound (b)>
[0130] The compound (b) is at least one compound selected from the group consisting of a boron compound, a bismuth compound, and a phosphorus compound. Among them, a boron compound is preferred from the viewpoint of further exerting the effects of the present invention.
[0131] In addition, compound (b) is a compound different from compound (a).
[0132] The compound (b) contained in the present material may be one kind or two or more kinds.
[0133] From the viewpoint of easy handling, the compound (b) is preferably an inorganic compound, more preferably a compound containing lithium or hydrogen as a constituent element, and still more preferably a composite oxide containing lithium as a constituent element.
[0134] The compound (b) can be produced by a conventionally known method, or a commercially available product can be used.
[0135] The compound (b) before the pulverization and mixing is preferably a crystalline compound. Whether the compound (b) is a crystalline compound can be determined, for example, from the X-ray diffraction (XRD) pattern of the compound (b).
[0136] Examples of boron compounds include LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 , Li 3.6 B2O 4.8 , Li 3.2 B2O 4.6 、Li4B2O5、Li6B4O9、Li 3-x5 B 1-x5 C x5 O3(0<x5<1), Li 4-x6 B 2-x6 C x6 O5(0<x6<2), Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1Among them, Li3BO3, Li 3.6 B2O 4.8 , Li 3.2 B2O 4.6 , Li4B2O5, LiBO2, LiB3O5, more preferably Li3BO3, Li4B2O5.
[0137] Examples of bismuth compounds include LiBiO2, Li3BiO3, Li4Bi2O5, Li 2.4 Al 0.2 Among them, LiBiO2 and Li3BiO3 are preferred, and LiBiO2 is more preferred, because they can lower the sintering temperature when obtaining a sintered body with sufficient ion conductivity.
[0138] Examples of the phosphorus compound include LiPO 3 and Li 3 PO 4 . Among them, LiPO 3 is preferred because it can lower the sintering temperature when obtaining a sintered body having sufficient ion conductivity.
[0139] [Method for producing compound (b)]
[0140] The method for producing the compound (b) is not particularly limited, and for example, a conventionally known production method such as a solid phase reaction or a liquid phase reaction can be used. Specific examples of the production method include a method comprising a mixing step and a calcining step.
[0141] In addition, as the compound (b), a commercially available product can be used.
[0142] Mixing process
[0143] As the mixing step, for example, when producing a composite oxide containing lithium as a constituent element, a lithium atom-containing compound as a raw material is mixed with a boron atom-containing compound, a bismuth atom-containing compound, or a phosphorus atom-containing compound.
[0144] Depending on the type of compound (b), this mixing step may not be performed.
[0145] The compound containing lithium atoms is not particularly limited, but is preferably an inorganic compound from the perspective of easy handling. Examples of inorganic compounds containing lithium atoms include lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium hydroxide (LiOH), lithium acetate (LiCH3COO), and hydrates thereof. Among them, lithium carbonate is preferred from the perspective of easy decomposition and reaction. In addition, lithium hydroxide monohydrate (LiOH·H2O) is also preferably used.
[0146] The lithium atom-containing compound may be used alone or in combination of two or more.
[0147] The compound containing a boron atom is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples of the inorganic compound containing a boron atom include boric acid (H3BO3) and boron oxide (B2O3). Among them, boric acid is preferred.
[0148] The boron atom-containing compound may be used alone or in combination of two or more.
[0149] The compound containing bismuth atoms is not particularly limited, but is preferably an inorganic compound from the viewpoint of easy handling, and examples of inorganic compounds containing bismuth atoms include bismuth oxide and bismuth nitrate (Bi(NO3)3). Among them, bismuth oxide is preferred.
[0150] The bismuth atom-containing compound may be used alone or in combination of two or more.
[0151] The phosphorus atom-containing compound is not particularly limited, but phosphates are preferred. Examples of the phosphates include diammonium hydrogen phosphate ((NH4)2HPO4) and monoammonium dihydrogen phosphate (NH4H2PO4) from the viewpoint of easy decomposition and reaction.
[0152] The phosphorus atom-containing compound may be used alone or in combination of two or more.
[0153] Examples of a method for mixing the raw materials include a method of mixing using a roll mill, a ball mill, a small diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank disintegrator, a jet mill, and the like.
[0154] The mixing ratio of the raw materials may be, for example, a stoichiometric ratio that can give a desired composition of the compound (b).
[0155] In addition, in the calcination step described later, since lithium atoms are easy to flow out of the system, the above-mentioned lithium atom-containing compound can be used in excess of about 10% to 20%. In addition, in the calcination step described later, in order to suppress the generation of by-products, when the above-mentioned phosphorus atom-containing compound is used, the compound can be used in excess of about 0.1% to 10%.
[0156] During the mixing, the mixture may be mixed while being heated as necessary, but is usually mixed at room temperature.
[0157] The mixing may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.
[0158] ·Firing process
[0159] In the calcining step, the mixture obtained in the mixing step is calcined. When the calcining step is performed multiple times, a pulverizing step using a ball mill, a mortar or the like may be provided in order to pulverize or reduce the particle size of the calcined product obtained in the calcining step.
[0160] The calcining step may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon gas whose oxygen content is adjusted to a range of 0 to 20% by volume.
[0161] The calcination temperature varies depending on the calcination time, but is preferably 400 to 1000°C, more preferably 500 to 900°C.
[0162] When the calcination temperature is within the above range, lithium atoms are less likely to flow out of the system, and the desired compound (b) tends to be easily obtained.
[0163] The firing time (the total firing time when the firing process is performed several times) varies depending on the firing temperature, but is preferably 1 to 48 hours, and more preferably 3 to 24 hours.
[0164] When the calcination time is within the above range, lithium atoms are less likely to flow out of the system, and the desired compound (b) tends to be easily obtained.
[0165] The fired product obtained after the firing step may absorb moisture or react with carbon dioxide to deteriorate if left in the air. Therefore, the fired product obtained after the firing step is preferably transferred to a dehumidified inert gas atmosphere for storage when the temperature reaches 200° C. or less during the temperature drop after the firing step.
[0166] From the viewpoint of being able to lower the sintering temperature when obtaining a sintered body with sufficient ion conductivity, the content of compound (b) in the present material is preferably 1 to 40 mol%, more preferably 3 to 30 mol%, and even more preferably 5 to 20 mol%, relative to 100 mol% of the total of compounds (a) and (b).
[0167] <Other ingredients>
[0168] The present material is not particularly limited as long as it contains compound (a) and compound (b), and may contain other components in addition to compound (a) and (b). As such other components, there may be cited previously known materials used in solid electrolytes of all-solid batteries, for example, lithium ion conductive compounds other than compound (a), sintering aids other than compound (b), and aluminum oxide (Al2O3).
[0169] The above-mentioned other components may be used alone or in combination of two or more.
[0170] The content of the above-mentioned other components in the present material is preferably 40% by mass or less, more preferably 30% by mass or less, based on 100% by mass of the total of compounds (a) and (b). The present material preferably does not contain the above-mentioned other components.
[0171] <Manufacturing method of this material>
[0172] The present material can be manufactured, for example, by a method comprising a step of mixing compound (a) and compound (b). When a solid electrolyte is obtained from the present material, it is preferably manufactured by a method comprising a step of crushing and mixing compound (a) and compound (b), from the perspective of being able to easily obtain a solid electrolyte having higher ion conductivity.
[0173] When the compound (a) and the compound (b) are pulverized and mixed, it is preferred that the pulverization and mixing be performed so that the obtained present material becomes amorphous by a mechanochemical reaction and / or so that the average particle size of the present material falls within the above range.
[0174] As a method for mixing compound (a) and compound (b), for example, there can be mentioned a method of mixing using a rolling mill, a ball mill, a small diameter ball mill (bead mill), a medium stirring mill, a jet mill, a mortar, an automatic mixing mortar, a tank disintegrator, a jet mill, etc. Among them, from the perspectives of being able to mix compound (a) and compound (b) powder, and being able to easily obtain a solid electrolyte having higher ion conductivity when a solid electrolyte is obtained from this material, a method of pulverizing and mixing using a ball mill or a bead mill is preferred, and a method of pulverizing and mixing using a ball mill with balls having a diameter of 0.1 to 10 mm is more preferred.
[0175] The compound (a) and the compound (b) are preferably mixed in such an amount that the content of the compound (b) falls within the above range.
[0176] The pulverization and mixing time is preferably 1 to 12 hours, more preferably 2 to 12 hours, from the viewpoint of being able to uniformly pulverize and mix the compound (a) and the compound (b) and easily obtaining an amorphous material having an average particle size (D50) within the above range.
[0177] During the pulverization and mixing, the pulverization and mixing may be performed while being heated as necessary, but the pulverization and mixing is usually performed at room temperature.
[0178] The pulverization and mixing may be performed in the air, preferably in an atmosphere of nitrogen and / or argon with an oxygen content adjusted to a range of 0 to 20% by volume.
[0179] Solid Electrolytes
[0180] A solid electrolyte according to an embodiment of the present invention (hereinafter also referred to as “present electrolyte”) is obtained using the present material described above, and is preferably a sintered body of the present material obtained by sintering the present material.
[0181] The electrolyte preferably has a monoclinic structure. Whether the solid electrolyte has a monoclinic structure can be determined, for example, by performing a Rietveld analysis on an X-ray diffraction (XRD) pattern of the solid electrolyte. Specifically, the determination can be made using the method of the following embodiment.
[0182] The monoclinic ratio of the present electrolyte (=monoclinic crystal amount×100 / total observed crystal amount) is preferably 70% or more, more preferably 80% or more, further preferably 90% or more, and the upper limit is not particularly limited but is 100%.
[0183] When the monoclinic fraction of the present electrolyte is within the above range, the electrolyte tends to be a solid electrolyte having high ion conductivity both within the crystal grains and at the grain boundaries.
[0184] The relative density of the present electrolyte is preferably 60 to 100%, more preferably 80 to 100%, from the viewpoint of being able to easily obtain a solid electrolyte with higher ion conductivity.
[0185] The relative density is specifically measured by the following method.
[0186] The mass of the prepared solid electrolyte was measured using an electronic balance. Next, the volume was measured using a micrometer based on the actual size of the solid electrolyte. The density (measured value) of the solid electrolyte can be calculated by dividing the measured mass by the volume, and the relative density (%) can be calculated based on the ratio of the theoretical value of the density of the solid electrolyte to the measured value.
[0187] Furthermore, specifically, the theoretical density of the solid electrolyte can be calculated by taking a weighted average using the theoretical density of the crystal structure constituting the solid electrolyte and the content of the crystal structure. For example, when the solid electrolyte has a crystal structure 1 with a content of h% and a crystal structure 2 with a content of k%, it can be calculated by (theoretical density of crystal structure 1 × h + theoretical density of crystal structure 2 × k) / 100.
[0188] The content of each crystal structure can be determined by Rietveld analysis.
[0189] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 850°C or higher and 900°C or lower is preferably 2.00×10 -4 S cm -1 More preferably, 3.00×10 -4 S cm -1 above.
[0190] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 750°C or higher and lower than 850°C is preferably 2.00×10 -5 S cm -1 More preferably, 4.00×10 -5 S cm -1 above.
[0191] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 700°C or higher and lower than 750°C is preferably 1.00×10 -5 S cm -1 More preferably, 2.00×10 -5 S cm -1 above.
[0192] The total ion conductivity of the sintered body of the present material obtained by sintering the present material at 650°C or higher and lower than 700°C is preferably 1.00×10 -6 S cm -1 More preferably, 2.00×10 -6 S cm -1 above.
[0193] When the total ion conductivity is within the above range, it can be said that a sintered body obtained by sintering the present material at a low temperature has sufficient ion conductivity.
[0194] The total ion conductivity can be specifically measured by the method described in the following examples.
[0195] 《Method for producing solid electrolyte》
[0196] A method for producing a solid electrolyte (the present electrolyte production method) according to one embodiment of the present invention preferably includes a step A of sintering the present material, and more preferably a method of forming the present material and then sintering it to form a sintered body.
[0197] The calcination temperature in the step A is preferably 500 to 900°C, more preferably 600 to 900°C, and even more preferably 650 to 900°C.
[0198] Since this material is used, a sintered body having sufficient ion conductivity can be obtained even when sintering is performed at such a low temperature.
[0199] The calcination time in the step A varies depending on the calcination temperature, but is preferably 12 to 144 hours, and more preferably 48 to 96 hours.
[0200] When the calcination time is within the above range, a sintered body having sufficient ion conductivity can be obtained even when calcination is performed at a low temperature.
[0201] The calcination in the step A may be performed in the air, but is preferably performed in an atmosphere of nitrogen and / or argon with the oxygen content adjusted to a range of 0 to 20% by volume.
[0202] In addition, the calcination in the above step A can also be performed under a reducing gas atmosphere such as a nitrogen-hydrogen mixed gas containing a reducing gas such as hydrogen. The ratio of hydrogen contained in the nitrogen-hydrogen mixed gas can be, for example, 1 to 10% by volume. As the reducing gas, in addition to hydrogen, ammonia gas, carbon monoxide gas, etc. can also be used.
[0203] In the above step A, from the viewpoint of being able to easily obtain a solid electrolyte (sintered body) with higher ion conductivity, it is preferred to sinter a body obtained by molding the present material, and it is more preferred to sinter a body obtained by press molding the present material.
[0204] The pressure during press molding of the present material is not particularly limited, but is preferably 50 to 500 MPa, more preferably 100 to 400 MPa.
[0205] The shape of the molded body obtained by press-molding the present material is not particularly limited, but is preferably a shape corresponding to the use of the sintered body (solid electrolyte) obtained by sintering the molded body.
[0206] A method for producing a solid electrolyte according to one embodiment of the present invention (the method for producing the present electrolyte) comprises:
[0207] Step 1 of preparing an amorphous solid electrolyte material by pulverizing and mixing a lithium ion conductive compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one compound (b) selected from a boron compound, a bismuth compound and a phosphorus compound [the compound (b) is a compound different from the compound (a)]; and
[0208] The solid electrolyte material obtained in step 1 is subjected to step 2 for calcining.
[0209] In particular, when both the lithium ion conductive compound (a) and the compound (b) are crystalline, at least two compounds which are crystalline themselves are crushed and mixed and temporarily become amorphous through a mechanochemical reaction, and the amorphous material is sintered, thereby easily obtaining a solid electrolyte with high ion conductivity.
[0210] As the lithium ion conductive compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements, there can be mentioned the same compounds as the compound (a) listed in the above-mentioned solid electrolyte material, and as the compound (b), there can be mentioned the same compounds as the compound (b) listed in the above-mentioned solid electrolyte material.
[0211] As step 1, the same steps as those exemplified in the above-mentioned method for producing the present material can be mentioned, and as step 2, the same steps as the above-mentioned step A can be mentioned.
[0212] In addition, when manufacturing the present electrolyte, other components other than the present material may also be used. As the other components, the previously known materials used in the solid electrolyte of the all-solid battery may be cited, for example, as the lithium ion conductive compound, the lithium ion conductive materials having structures such as NASICON type and LISICON type may be cited.
[0213] The above-mentioned other components may be used alone or in combination of two or more.
[0214] The amount of the other components used is preferably 50% by mass or less, more preferably 30% by mass or less, based on 100% by mass of the total amount of the other components and the present material. It is preferred that the other components are not used.
[0215] All-solid-state battery
[0216] An all-solid-state battery (hereinafter also referred to as "the present battery") involved in one embodiment of the present invention comprises a positive electrode having a positive electrode active material, a negative electrode having a negative electrode active material, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the solid electrolyte layer comprises the present electrolyte.
[0217] The present battery may be a primary battery or a secondary battery, but is preferably a secondary battery, and more preferably a lithium ion secondary battery, from the viewpoint of further exerting the effects of the present invention.
[0218] The structure of the present battery is not particularly limited as long as it includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, and may be any of a so-called thin film type, a laminated type, and a bulk type.
[0219] <Solid electrolyte layer>
[0220] The solid electrolyte layer is not particularly limited as long as it contains the present electrolyte, and may contain conventionally known additives used in the solid electrolyte layer of an all-solid-state battery as necessary, but is preferably composed of the present electrolyte.
[0221] The thickness of the solid electrolyte layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 50 nm to 1000 μm, and more preferably 100 nm to 100 μm.
[0222] <Positive electrode>
[0223] The positive electrode is not particularly limited as long as it has a positive electrode active material, but preferably, a positive electrode having a positive electrode collector and a positive electrode active material layer is used.
[0224] [Positive electrode active material layer]
[0225] The positive electrode active material layer is not particularly limited as long as it contains a positive electrode active material, but preferably contains a positive electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid.
[0226] The thickness of the positive electrode active material layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 10 to 200 μm, more preferably 30 to 150 μm, and further preferably 50 to 100 μm.
[0227] Positive electrode active material
[0228] Examples of positive electrode active materials include LiCo oxide, LiNiCo oxide, LiNiCoMn oxide, LiNiMn oxide, LiMn oxide, LiMn spinel, LiMnNi oxide, LiMnAl oxide, LiMnMg oxide, LiMnCo oxide, LiMnFe oxide, LiMnZn oxide, LiCrNiMn oxide, LiCrMn oxide, lithium titanate, lithium metal phosphate, transition metal oxides, titanium sulfide, graphite, hard carbon, lithium nitride containing transition metals, silicon oxide, lithium silicate, lithium metal, lithium alloy, solid solution containing Li, and lithium storage metal compounds.
[0229] Among them, LiNiCoMn oxide, LiNiCo oxide, and LiCo oxide are preferred, and LiNiCoMn oxide is more preferred, from the perspectives of good affinity with solid electrolytes, excellent balance among macroscopic conductivity, microscopic conductivity and ionic conductivity, high average potential, and the ability to improve energy density or battery capacity in a balance between specific capacity and stability.
[0230] Alternatively, the positive electrode active material may be surface-coated with lithium niobate, lithium phosphate, lithium borate, or the like, which is an ion-conductive oxide.
[0231] The positive electrode active material used in the positive electrode active material layer may be one kind or two or more kinds.
[0232] Preferred examples of the positive electrode active material include LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4、Li4Ti5O 12 .
[0233] The positive electrode active material is preferably in a particle form, and the 50% diameter in the volume-based particle size distribution is preferably 0.1 to 30 μm, more preferably 0.3 to 20 μm, further preferably 0.4 to 10 μm, and particularly preferably 0.5 to 3 μm.
[0234] The ratio of the major axis length to the minor axis length (major axis length / minor axis length) of the positive electrode active material, that is, the aspect ratio, is preferably less than 3, and more preferably less than 2.
[0235] The positive electrode active material may be in the form of secondary particles. In this case, the 50% diameter in the number-based particle size distribution of the primary particles is preferably 0.1 to 20 μm, more preferably 0.3 to 15 μm, further preferably 0.4 to 10 μm, and particularly preferably 0.5 to 2 μm.
[0236] The content of the positive electrode active material in the positive electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.
[0237] When the content of the positive electrode active material is within the above range, the positive electrode active material functions well, and there is a tendency that a battery with high energy density can be easily obtained.
[0238] Solid electrolyte
[0239] The solid electrolyte that can be used in the positive electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, the present electrolyte is preferably used from the viewpoint of further exerting the effects of the present invention.
[0240] The solid electrolyte used in the positive electrode active material layer may be one kind or two or more kinds.
[0241] ·additive
[0242] Preferred examples of the conductive additive include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and carbon nanofibers.
[0243] As the sintering aid, the same compounds as the compound (b) exemplified in the above-mentioned solid electrolyte material are preferred.
[0244] The additives used in the positive electrode active material layer may be one kind or two or more kinds.
[0245] Positive electrode collector
[0246] The positive electrode current collector is not particularly limited as long as its material is a material that conducts electrons without inducing an electrochemical reaction. As the material of the positive electrode current collector, for example, conductive metal oxides such as copper, aluminum, and iron, alloys containing these metals, antimony-doped tin oxide (ATO), and tin-doped indium oxide (ITO) can be cited.
[0247] In addition, as the positive electrode current collector, a current collector having a conductive adhesive layer provided on the surface of the current collector may be used. Examples of the conductive adhesive layer include a layer containing a granular conductive material or a fibrous conductive material.
[0248] <Negative electrode>
[0249] The negative electrode is not particularly limited as long as it has a negative electrode active material, but preferably, a negative electrode has a negative electrode collector and a negative electrode active material layer.
[0250] [Negative Electrode Active Material Layer]
[0251] The negative electrode active material layer is not particularly limited as long as it contains a negative electrode active material, but preferably contains a negative electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid.
[0252] The thickness of the negative electrode active material layer can be appropriately selected depending on the structure of the battery to be formed (thin film type, etc.), and is preferably 10 to 200 μm, more preferably 30 to 150 μm, and further preferably 50 to 100 μm.
[0253] Negative electrode active material
[0254] Examples of the negative electrode active material include lithium alloys, metal oxides, graphite, hard carbon, soft carbon, silicon, silicon alloys, silicon oxide SiO n (0<n≤2), silicon / carbon composite material, composite material containing silicon domains in pores of porous carbon, lithium titanate, and graphite coated with lithium titanate.
[0255] Among them, silicon / carbon composite materials and composite materials containing silicon domains in the pores of porous carbon have high specific capacity, can improve energy density and battery capacity, and are therefore preferred. More preferably, a composite material containing silicon domains in the pores of porous carbon has excellent slackness in volume expansion of silicon accompanying lithium absorption / release, and can well maintain the balance of macroscopic conductivity, microscopic conductivity and ion conductivity. Particularly preferred is a composite material in which the silicon domain is amorphous, the size of the silicon domain is less than 10nm, there are pores from porous carbon near the silicon domain, and the silicon domain is contained in the pores of porous carbon.
[0256] Preferred examples of the negative electrode active material include LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi, graphite.
[0257] The negative electrode active material is preferably in particulate form, and its 50% diameter in volume-based particle size distribution, aspect ratio, and 50% diameter in number-based particle size distribution of primary particles when the negative electrode active material forms secondary particles are preferably in the same range as those of the positive electrode active material.
[0258] The content of the negative electrode active material in the negative electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.
[0259] When the content of the negative electrode active material is within the above range, the negative electrode active material functions well, and there is a tendency that a battery with high energy density can be easily obtained.
[0260] Solid electrolyte
[0261] The solid electrolyte that can be used in the negative electrode active material layer is not particularly limited, and any conventionally known solid electrolyte can be used. However, the present electrolyte is preferably used from the viewpoint of further exerting the effects of the present invention.
[0262] The solid electrolyte used in the negative electrode active material layer may be one kind or two or more kinds.
[0263] ·additive
[0264] Preferred examples of the conductive additive include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and carbon nanofibers.
[0265] As the sintering aid, the same compounds as the compound (b) exemplified in the above-mentioned solid electrolyte material are preferred.
[0266] The additives used in the negative electrode active material layer may be one kind or two or more kinds.
[0267] Negative electrode collector
[0268] As the negative electrode current collector, the same current collector as the positive electrode current collector can be used.
[0269] <Method for manufacturing all-solid-state battery>
[0270] All-solid batteries can be formed, for example, by a known powder molding method. For example, a positive electrode collector, a positive electrode active material layer powder, a solid electrolyte layer powder, a negative electrode active material layer powder, and a negative electrode collector are sequentially overlapped and powder molded at the same time, thereby simultaneously forming each layer of a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, and connecting each of the positive electrode collector, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, and the negative electrode collector.
[0271] When the powder is molded, it is preferred that the powder is fired at the same temperature as the firing temperature in the above step A while applying a pressure of the same degree as the pressure used when the material is press-molded in the above step A.
[0272] According to one embodiment of the present invention, even if the firing temperature during the manufacture of the all-solid-state battery is low, an all-solid-state battery with sufficient ion conductivity can be obtained, thereby being able to suppress the decomposition or deterioration of other materials such as positive electrode or negative electrode materials, thereby enabling the all-solid-state battery to be manufactured in an economical and equipment-saving manner.
[0273] Alternatively, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer may be individually subjected to the above-mentioned powder molding, and when using the obtained layers to make an all-solid-state battery, each layer is preferably pressed and fired.
[0274] In addition, the all-solid-state battery can also be produced by the following method, for example.
[0275] By appropriately mixing a solvent, a resin, etc. in a material for forming a positive electrode active material layer, a material for forming a solid electrolyte layer, and a material for forming a negative electrode active material layer, a paste for forming each layer is prepared, and the paste is applied on a substrate and dried to produce a green sheet for a positive electrode active material layer, a green sheet for a solid electrolyte layer, and a green sheet for a negative electrode active material layer. Next, the substrate is peeled off from each green sheet, and the green sheet for the positive electrode active material layer, the green sheet for the solid electrolyte layer, and the green sheet for the negative electrode active material layer are sequentially stacked, and after being heat-pressed at a predetermined pressure, they are sealed in a container and pressurized by hot isostatic pressing, cold isostatic pressing, hydrostatic pressing, etc., to produce a stacked structure.
[0276] Then, if necessary, the stacked structure is subjected to a degreasing treatment at a predetermined temperature and then subjected to a sintering treatment to produce a stacked sintered body.
[0277] The firing temperature in this firing treatment is preferably the same temperature as the firing temperature in the above-mentioned step A.
[0278] Next, as necessary, a positive electrode current collector and a negative electrode current collector may be formed on both main surfaces of the stacked sintered body by sputtering, vacuum deposition, coating or dipping of a metal paste, etc., thereby producing an all-solid-state battery.
[0279] Example
[0280] Hereinafter, the present invention will be described in detail based on examples. However, the present invention is not limited to these examples.
[0281] <Powder X-ray Diffraction (XRD)>
[0282] The powder and solid electrolyte material obtained in the following synthesis example were subjected to X-ray diffraction measurement using a powder X-ray diffraction measuring apparatus Panalytical MPD (manufactured by Spectris Corporation) (Cu-Kα ray (output: 45 kV, 40 mA), diffraction angle 2θ=10 to 50°, step width: 0.013°, incident side Sollerslit: 0.04 rad, incident side Anti-scatter slit: 2°, light receiving side Sollerslit: 0.04 rad, light receiving side Anti-scatter slit: 5 mm), and an X-ray diffraction (XRD) pattern was obtained. The obtained XRD pattern was subjected to Rietveld analysis using the known analysis software RIETAN-FP (available from the homepage of the creator Fujio Izumi, "RIETAN-FP·VENUS System Distribution File" (http: / / fujioizumi.verse.jp / download / download.html)), thereby confirming the crystal structure.
[0283] [Synthesis Example 1] Synthesis of LiTa2PO8
[0284] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 99.9%), and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, purity of 98% or more) were weighed so that the atomic ratio of lithium, tantalum, and phosphorus (Li:Ta:P) was 1.10:2.00:1.06. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: diameter 1 mm).
[0285] The obtained mixture was placed in an alumina container and heated to 1000°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 1000°C for 4 hours to obtain a primary sintered product.
[0286] The primary fired product was crushed and mixed in an agate mortar for 15 minutes, and the mixture was placed in an alumina container. The mixture was heated to 1000°C at a rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 1000°C for 1 hour to obtain a secondary fired product (LiTa2PO8).
[0287] The obtained secondary fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.
[0288] The XRD pattern of the obtained secondary fired product is shown in Figure 1 According to the XRD pattern, only a monoclinic diffraction pattern substantially the same as that of LiTa2PO8 was observed for the obtained secondary calcined product, and the monoclinic ratio (=monoclinic crystal amount×100 / total crystal amount observed) was 100%.
[0289] [Synthesis Example 2] LTPO (Li containing Si 1.2 Ta2P 0.8 Si 0.2 Synthesis of O8)
[0290] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich with a purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. with a purity of 99.9%), diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich with a purity of 98% or more), and silicon oxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. with a purity of 99.9%) were weighed so that the atomic ratio of lithium, tantalum, phosphorus and silicon (Li:Ta:P:Si) was 1.38:2.00:0.85:0.20. Otherwise, the preparation was carried out in the same manner as in Synthesis Example 1 to obtain a secondary fired product (referred to as Si-containing LTPO for short).
[0291] The XRD pattern of the obtained secondary fired product is shown in Figure 2 According to the XRD pattern, the obtained secondary fired product was a crystal having a monoclinic crystal ratio of 100%.
[0292] [Synthesis Example 3] LTPO (LiTa containing Nb 1.8 Nb 0.2 Synthesis of PO8
[0293] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich with a purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. with a purity of 99.9%), diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich with a purity of 98% or more), and niobium pentoxide (Nb2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. with a purity of 99.9%) were weighed so that the atomic ratio of lithium, tantalum, phosphorus and niobium (Li:Ta:P:Nb) was 1.10:1.80:1.06:0.20. Otherwise, the preparation was carried out in the same manner as in Synthesis Example 1 to obtain a secondary fired product (referred to as Nb-containing LTPO for short).
[0294] The XRD pattern of the obtained secondary fired product is shown in Figure 3 According to the XRD pattern, the obtained secondary fired product was a crystal having a monoclinic crystal ratio of 100%.
[0295] [Synthesis Example 4] Synthesis of Li3BO3
[0296] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) were weighed so that the atomic ratio of lithium to boron (Li:B) was 3.00:1.00. The weighed raw material powders were pulverized and mixed in an agate mortar for 15 minutes to obtain a mixture.
[0297] The obtained mixture was placed in an alumina container and heated to 500°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 500°C for 2 hours to obtain a primary sintered product.
[0298] The primary fired product was crushed and mixed in an agate mortar for 15 minutes, and the mixture was placed in an alumina container. The temperature was raised to 630°C at a heating rate of 10°C / min in a rotary sintering furnace (manufactured by Motoyama Co., Ltd.) in an atmosphere of air (flow rate: 100 mL / min), and the product was sintered at 630°C for 24 hours to obtain a secondary fired product (Li3BO3).
[0299] The obtained secondary fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.
[0300] From the XRD pattern of the obtained secondary fired product, it was found that the obtained secondary fired product was crystalline.
[0301] [Synthesis Example 5] Synthesis of Li4B2O5
[0302] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) are weighed so that the atomic ratio of lithium to boron (Li:B) becomes 2.00:1.00, and the preparation is carried out in the same manner as in Synthesis Example 4, to obtain a secondary calcined product (Li4B2O5).
[0303] From the XRD pattern of the obtained secondary fired product, it was found that the obtained secondary fired product was crystalline.
[0304] [Synthesis Example 6] Li 3.6 B2O 4.8 Synthesis
[0305] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) were weighed so that the atomic ratio of lithium to boron (Li:B) was 1.80:1.00, and the same method as in Synthesis Example 4 was used to obtain a secondary calcined product (Li 3.6 B2O 4.8 ).
[0306] From the XRD pattern of the obtained secondary fired product, it was found that the obtained secondary fired product was crystalline.
[0307] [Synthesis Example 7] Li 3.2 B2O 4.6 Synthesis
[0308] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more) and boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more) were weighed so that the atomic ratio of lithium to boron (Li:B) was 1.60:1.00, and the same method as in Synthesis Example 4 was used to obtain a secondary calcined product (Li 3.2 B2O 4.6 ).
[0309] From the XRD pattern of the obtained secondary fired product, it was found that the obtained secondary fired product was crystalline.
[0310] [Synthesis Example 8] Li 3.6 B 1.6 C 0.4 Synthesis of O5
[0311] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 98.0% or more), boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.5% or more), and lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, with a purity of 99.0% or more) were weighed so that the atomic ratio of lithium, boron, and carbon (Li:B:C) was 3.6:1.6:0.4. The weighed raw material powders were pulverized and mixed in an agate mortar for 15 minutes to obtain a mixture.
[0312] The obtained mixture was prepared in the same manner as in Synthesis Example 4 to obtain a secondary fired product (Li 3.6 B1.6 C 0.4 O5).
[0313] The XRD pattern of the obtained fired product revealed that the obtained fired product was crystalline.
[0314] [Synthesis Example 9] Synthesis of LiPO3
[0315] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, with a purity of 99.0% or more) and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, with a purity of 98% or more) were weighed so that the atomic ratio of lithium to phosphorus (Li:P) was 1:1. The weighed raw material powders were crushed and mixed in an agate mortar for 15 minutes to obtain a mixture.
[0316] The obtained mixture was placed in an alumina container and heated to 600°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 600°C for 3 hours to obtain a sintered product (LiPO3).
[0317] The obtained fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.
[0318] The XRD pattern of the obtained fired product revealed that the obtained fired product was crystalline.
[0319] [Synthesis Example 10] Synthesis of LiBiO2
[0320] Lithium hydroxide monohydrate (LiOH·H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 98.0% or more) and bismuth oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity of 99.9%) were weighed so that the atomic ratio of lithium to bismuth (Li:Bi) was 1:1. The weighed raw material powders were pulverized and mixed in an agate mortar for 15 minutes to obtain a mixture.
[0321] The obtained mixture was placed in an alumina container and heated to 600°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.), and sintered at 600°C for 4 hours to obtain a sintered product (LiBiO2).
[0322] The obtained fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.
[0323] The XRD pattern of the obtained fired product revealed that the obtained fired product was crystalline.
[0324] [Synthesis Example 11]H3BO3
[0325] Commercially available boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.5% or more) was used as it is.
[0326] [Example 1]
[0327] LiTa2PO8 obtained in Synthesis Example 1 and Li3BO3 obtained in Synthesis Example 4 were weighed at a molar ratio (LiTa2PO8:Li3BO3) of 0.975:0.025. The weighed compounds were placed in a zirconia ball mill, and an appropriate amount of toluene was added thereto, and pulverized and mixed for 2 hours using zirconia balls with a diameter of 1 mm, thereby obtaining a solid electrolyte material (mixture).
[0328] The XRD pattern of the obtained solid electrolyte material is shown in Figure 4 The XRD pattern shows that the obtained solid electrolyte material is amorphous.
[0329] <Production of pellets>
[0330] A tablet molding machine was used to apply a pressure of 40 MPa to the obtained solid electrolyte material using a hydraulic press, thereby forming a disc-shaped molded body with a diameter of 10 mm and a thickness of 1 mm. Then, a pressure of 300 MPa was applied to the disc-shaped molded body by CIP (cold isostatic pressing) to produce particles.
[0331] <Production of sintered body>
[0332] The obtained particles were placed in an alumina container and heated to 850°C at a rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by Motoyama Co., Ltd.). The mixture was sintered at this temperature for 96 hours to obtain a sintered body serving as a solid electrolyte.
[0333] The obtained fired product was cooled to room temperature, taken out from the rotary firing furnace, and stored in a dehumidified nitrogen atmosphere.
[0334] <Total conductivity>
[0335] A gold layer was formed on both surfaces of the obtained sintered body using a sputtering machine, thereby obtaining measurement particles for evaluating ion conductivity.
[0336] The obtained measured particles were kept in a constant temperature bath at 25°C for 2 hours before measurement. Then, at 25°C, an impedance analyzer (Solartron Analytical, model: 1260A) was used to perform AC impedance measurement in the range of 1Hz to 10MHz with an amplitude of 25mV. Using the equivalent circuit analysis software ZView attached to the device, the obtained impedance spectrum was fitted with an equivalent circuit to obtain the lithium ion conductivity in the grains and at the grain boundaries, and the total conductivity was calculated by summing them up. The results are shown in Table 1.
[0337] [Examples 2 to 10 and Comparative Example 1]
[0338] The solid electrolyte material was prepared in the same manner as in Example 1 except that the compound (a) described in Table 1 was used and the mixing amount of Li3BO3 and the calcination temperature were changed to those shown in Table 1. The obtained solid electrolyte material was then calcined at the calcination temperature described in Table 1, and the total conductivity of the obtained sintered body was measured. The results are shown in Table 1.
[0339] Furthermore, the results of XRD measurement of the solid electrolyte materials obtained in Examples 2 to 10 showed that the solid electrolyte materials were amorphous.
[0340]
[0341] As can be seen from Table 1, the solid electrolyte material comprising a lithium ion conductive compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements and a boron compound (Li3BO3) as a compound (b) can obtain a sintered body with sufficient ion conductivity even when sintered at a low temperature below 900°C.
[0342] [Examples 11 to 19]
[0343] The compound (a) described in Table 2 was used, and Li4B2O5 was used as the compound (b), and the mixing amount of Li4B2O5 and the calcination temperature were changed as shown in Table 2. A solid electrolyte material was prepared in the same manner as in Example 1, and then the obtained solid electrolyte material was calcined at the calcination temperature described in Table 2, and the total conductivity of the obtained sintered body was measured. The results are shown in Table 2.
[0344] In addition, the results of XRD measurement of the solid electrolyte materials obtained in Examples 11 to 19 respectively showed that they were amorphous.
[0345]
[0346] As can be seen from Table 2, the solid electrolyte material comprising a lithium ion conductive compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements and a boron compound (Li4B2O5) as a compound (b) can obtain a sintered body with sufficient ion conductivity even when sintered at a low temperature below 900°C.
[0347] [Examples 20 to 26]
[0348] The solid electrolyte material was prepared in the same manner as in Example 1 except that the compound (a) and (b) described in Table 3 were used and the mixing amount of the compound (b) and the calcination temperature were changed as shown in Table 3. The obtained solid electrolyte material was calcined at the calcination temperature described in Table 3, and the total conductivity of the obtained sintered body was measured. The results are shown in Table 3.
[0349] In addition, the results of XRD measurement of the solid electrolyte materials obtained in Examples 20 to 26 showed that they were amorphous.
[0350]
[0351] As can be seen from Table 3, a solid electrolyte material comprising a lithium ion conductive compound (a) containing lithium, tantalum, phosphorus and oxygen as constituent elements and at least one compound (b) selected from a boron compound, a bismuth compound and a phosphorus compound can obtain a sintered body with sufficient ion conductivity even when sintered at a low temperature below 900°C.
[0352] Industrial Availability
[0353] A solid electrolyte material according to one embodiment of the present invention can obtain a sintered body having sufficient ion conductivity even when sintered at a low temperature (eg, 900° C. or lower), and can be suitably used as a solid electrolyte for lithium ion secondary batteries.
Claims
1. A solid electrolyte material comprising a lithium ion conductive compound (a) and a compound (b), The lithium ion conductive compound (a) contains lithium, tantalum, phosphorus and oxygen as constituent elements, The compound (b) is at least one compound selected from a boron compound, a bismuth compound, and a phosphorus compound, and is different from the lithium ion conductive compound (a), The solid electrolyte material is amorphous.
2. The solid electrolyte material according to claim 1, The compound (a) has a monoclinic crystal structure.
3. The solid electrolyte material according to claim 1 or 2, The compound (a) is composed of the formula Li 1+(5-a)x 〕Ta 2-x M1 x PO8, or a compound having the formula Li〔 1+(5-b)y 〕Ta2P 1-y M2 y The compound represented by O8, in, M1 is one or more elements selected from Nb, Zr, Ga, Sn, Hf, W and Mo, 0.0≤x<1.0, a is the average valence of M1, M2 is one or more elements selected from Si, Al and Ge, 0.0≤y<0.7, and b is the average valence of M2.
4. The solid electrolyte material according to claim 1 or 2, The compound (b) contains lithium or hydrogen as a constituent element.
5. The solid electrolyte material according to claim 1 or 2, The content of tantalum element is 10.6 to 16.6 atomic %.
6. The solid electrolyte material according to claim 1 or 2, The content of phosphorus element is 5.3 to 8.3 atomic %.
7. The solid electrolyte material according to claim 1 or 2, The content of lithium element is 5.0 to 20.0 atomic %.
8. The solid electrolyte material according to claim 1 or 2, The boron compound is selected from LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 , Li 3.6 B2O 4.8 , Li 3.2 B2O 4.6 、Li4B2O5、Li6B4O9、Li 3-x5 B 1-x5 C x5 O3、Li 4-x6 B 2-x6 C x6 O5, Li 2.4 Al 0.2 BO3, Li 2.7 Al 0.1 At least one compound selected from BO3, B2O3 and H3BO3, 0<x5<1, 0<x6<2.
9. The solid electrolyte material according to claim 1 or 2, The bismuth compound is selected from LiBiO2, Li3BiO3, Li4Bi2O5, Li 2.4 Al 0.2 At least one compound of BiO3 and Bi2O3.
10. The solid electrolyte material according to claim 1 or 2, The phosphorus compound is at least one compound selected from LiPO3 and Li3PO4.
11. The solid electrolyte material according to claim 1 or 2, The content of the compound (b) is 1 to 40 mol % relative to 100 mol % of the total of the compounds (a) and (b).
12. A method for producing a solid electrolyte material, wherein the solid electrolyte material is the solid electrolyte material according to any one of claims 1 to 11, The production method includes the step of pulverizing and mixing the compound (a) and the compound (b). 13 . A solid electrolyte obtained by using the solid electrolyte material according to claim 1 . 14 . A solid electrolyte, which is a sintered body of the solid electrolyte material according to claim 1 . 15 . A method for producing a solid electrolyte, comprising the step of calcining the solid electrolyte material according to claim 1 at 500 to 900° C., wherein the solid electrolyte is the solid electrolyte according to claim 13 or 14.
16. A method for producing a solid electrolyte, comprising step 1 and step 2, In the step 1, a lithium ion conductive compound (a) and a compound (b) are pulverized and mixed to prepare an amorphous solid electrolyte material, wherein the lithium ion conductive compound (a) contains lithium, tantalum, phosphorus and oxygen as constituent elements, and the compound (b) is a compound different from the lithium ion conductive compound (a) and is at least one compound selected from a boron compound, a bismuth compound and a phosphorus compound. In the step 2, the solid electrolyte material obtained in the step 1 is calcined.
17. An all-solid-state battery comprising a positive electrode, a negative electrode and a solid electrolyte layer, The positive electrode has a positive electrode active material, The negative electrode has a negative electrode active material, The solid electrolyte layer is located between the positive electrode and the negative electrode, The solid electrolyte layer includes the solid electrolyte according to claim 13 or 14.
18. The all-solid-state battery according to claim 17, wherein the positive electrode active material comprises a material selected from the group consisting of LiM3PO4, LiM5VO4, Li2M6P2O7, LiVP2O7, Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO4)3、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 One or more compounds of M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O, M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, 2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, 0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge.
19. The all-solid-state battery according to claim 17 or 18, wherein the negative electrode active material comprises a material selected from the group consisting of LiM3PO4, LiM5VO4, Li2M6P2O7, LiVP2O7, Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO4)3、(Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1- y9 M10 y9 )O4, LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite, M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O, M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, 2≤x7≤4, 1≤y7≤3, 0≤z7≤1, 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, 0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge, M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0, 0≤y9≤0.6, a9 is the average price of M9, and b9 is the average price of M10.
20. The all-solid-state battery according to claim 17 or 18, The positive electrode and the negative electrode contain the solid electrolyte according to claim 13 or 14.
